Assessment of redundant randomized clinical trials among patients with ST segment elevation myocardial infarction - Yuanxi Jia; Jun Liang; Wenyao Wang; Xin Wei; Shaoming Xiao; Karen A. Robinson (BMC Medicine, 2023)
Abstract Background Redundant clinical trials waste resources and unnecessarily put patients at risk for harm. The objectives of the study were to assess redundant randomized clinical trials (RCTs) conducted in mainland China or the USA among patients with ST segment elevation myocardial infarction (STEMI) and estimate the harm to patients enrolled in redundant RCTs. Methods We searched bibliographic databases for eligible RCTs comparing a routine therapy with a placebo or no treatment among patients with STEMI in mainland China or the United States. The routine therapy for STEMI included reperfusion (percutaneous coronary intervention or fibrinolytic therapy), P2Y12 receptor inhibitors, statins, and anticoagulants. Redundant RCTs were defined as those initiated or continued recruiting new patients 1 year after the experimental intervention was established as routine therapy in clinical practice guidelines. Cumulative meta-analyses were conducted to confirm the efficacy of these routine therapies. The primary outcome was the number of extra major adverse cardiac events (MACEs) attributable to the deprivation of routine therapies among patients in the control groups of redundant RCTs—that is, the number of extra MACEs that could have been prevented had these patients received routine therapy. Results Nine hundred eighty-three eligible RCTs conducted in mainland China were identified, of which 775 (78.8%) were redundant. None of the five eligible RCTs conducted in the United States were redundant. All redundant RCTs have reiterated the benefits of routine therapies for patients with STEMI, while none were cited by the 2019 clinical practice guideline for the management of STEMI. The 18,819 patients in the control groups of redundant RCTs experienced 3305 (95% CI: 3169–3441) extra MACEs, including 1091 (1014–1165) deaths, 576 (519–633) recurrent myocardial infarctions, 31 (19–42) revascularizations, 39 (23–54) strokes, 744 (679–810) heart failures, and 823 (754–893) patients with recurrent or exacerbated angina pectoris. Cumulative meta-analyses confirmed the efficacy of the routine therapies among patients in mainland China and supported using practice guidelines to define redundant RCTs. Conclusions Redundant RCTs conducted in mainland China have resulted in unnecessary MACEs among patients with STEMI. While the reasons behind redundant RCTs need to be further investigated, these results suggest potential research waste and violation of research ethics.